Object oriented programming (OOP) and its relevance to designing intelligent software systems - Wechsler, H.; Rine, D. (Computer Languages, International Conference on (ICCL '88) 2nd: Proceedings, 1988)
The development of large software packages requires not only modularity but also the capability to experiment and change. Such a capability is akin to self-organization characteristics of adaptive systems. It is suggested that computer-aided software engineering (CASE) can benefit from the development retrainable software modules, where both the data structures and the algorithms performing on them are subject to evolutionary change. Such an approach is modeled after the AI (artificial-intelligence) methodology of reasoning by analogy, and it can be naturally implemented through the paradigm of object-oriented programming languages, which provide an exploratory software environment in which changes resulting from feedback to the system are easy to track and implement. The benefits of OOP to major software development areas involved with resource allocation, computer vision, and the service industry are discussed.< >